Satisfaction on Aerobic Dance - Choombuathong, Anchalee (Journal of Health Science of Thailand, 2018)
The objectives of this preliminary crossectional descriptive study were to assess satisfaction with aerobic dance as a means for health promotion. The data were analyzed by using descriptive statistics as frequency, mean percentage and standard deviation. Samples of 113 participants of aerobic dance exercise answered the questionnaire. They were mostly female, aged 21-40 years, employees of private companies with bachelor’s degree, having joined the exercise for more than 2 years, and participating with a frequency of more than 3 times per week. In a set of questionaire, degree of satisfaction was rated as 1-5 in score of the five choices and satisfaction on aerobic dance, and for health promotion, from 1 to 9. The results revealed that participants chose aerobic dance exercise primarily because it was fun dancing with music ( 4.24), it improved health ( 3.96). Instructors were able to create various steps and thus stimulating ( 3.37). The exercise also provided opportunity for socializing among all participants ( 3.21), and lastly it suited individual’s strength and endurance ( 3.11). They admitted that the most satisfaction was improving mental and physical health ( 3.53), followed by being relaxed and free from stress in the daily lives ( 3.46), increasing muscle strength and more strenuous work ( 3.42), strengthening heart and lung ( 3.41), improving attention and memory ( 3.38), improving physical fitness and immunity ( 3.37), improving sleep and resting ( 3.32), developing better muscle coordination and the nervous system ( 3.20), and controlling weight and keeping oneself in good shape ( 3.06). The results of this study can be applied to improve the promotion of exercise in the community.